The Importance of Regional and Landscape Context and Climate Change to Northern Bobwhite Management - Frank R. Thompson III (National Quail Symposium Proceedings, 2017)
Long-term declines in northern bobwhite (Colinus virginianus) in the United States are presumably due to decades of habitat loss or degradation at a national scale. Food and fiber production characterized by replacement of open woodlands and savannas by dense forest, intensification of agriculture, and conversion of native grasslands to nonnative pastures have degraded habitats for most grassland and early successional birds. Declines in bobwhite and associated species occurred within this context at a scale that has overwhelmed wildlife management efforts. However, with understanding of scale and context, managers could sustain these species in some future landscapes. Increasing urbanization over the next century will result in loss of millions of acres of forests, grasslands, and agricultural lands used by bobwhite and associated species, and climate change will affect abundance and distribution of shortleaf (Pinus echinata), loblolly (P. taeda), and longleaf (P. palustris) pine woodlands. I highlight modeling tools and planning efforts that demonstrate how conservation planning can address these changes. I suggest that focusing management in the correct landscape contexts and accounting for land use and climate change is more likely to be successful than management that does not and conservation partnerships and management efforts across public and private lands are required to affect regional bobwhite populations.
Keywords: climate change; colinus virginianus; northern bobwhite; LANDIS; landscape context; land use; prairie warbler; restoration; setophaga discolor